Distribution of Coefficients of Rank Polynomials for Random Sparse Graphs - Dmitry Jakobson; Calum MacRury; Sergey Norin; Lise Turner (The Electronic Journal of Combinatorics, 2018)
We study the distribution of coefficients of rank polynomials of random sparse graphs. We first discuss the limiting distribution for general graph sequences that converge in the sense of Benjamini-Schramm. Then we compute the limiting distribution and Newton polygons of the coefficients of the rank polynomial of random d-regular graphs.